Modelos masculinos y violencia en Sanctuary y Crónica de una muerte anunciada. - Valverde, César (2012)
This essay analyzes how two novels, William Faulkner’s Sanctuary and Gabriel Garcia Marquez’s Chronicle of a Death Foretold, present masculine models that juxtapose power and violence during times of social crisis. Both novels present violent masculinities that overcome peaceful masculinities, in conflicts that result in murders and rapes; but rather than acuse the individuals responsible for the violent acts, the texts point out the social mechanisms that inexorably move the authors of the crimes. In both works we also see violence against women and resulting public deaths of men wrongly accused, which happen due to an inability to adapt to a historical transition and a corresponding instance of masculine crisis. Horace Benbow and Bayardo San Roman, protagonists of these novels, fail and represent the defeat of masculinities based on reason and pasivity in the face of another masculinity constituted by violence and agression, since these latter ones are prescribed and accepted by society, even today.